PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM KASUS WANPRESTASI PERJANJIAN MELALUI MEDIA BELANJA ONLINE LAZADA - Aremanda Luis Marciano Manullang (2023)
This scientific study investigates the legal protection provided to consumers in cases of breach of contract through electronic media. Through normative legal analysis, the research examines relevant legislation and court rulings. The findings highlight that consumer protection in breach of contract cases involving electronic transactions is established in laws governing such transactions, like the Electronic Information and Transactions Act of 2008. The Act asserts consumers' rights to receive agreed-upon goods and services, along with compensation for losses incurred due to breach of contract. Institutions such as the Consumer Dispute Settlement Agency and the Consumer Court play essential roles in resolving consumer disputes arising from breach of contract incidents in electronic transactions. Challenges include difficulties in proving transaction agreements and violations by businesses, as well as the presence of irresponsible or elusive entities. To enhance consumer protection, the study recommends raising consumer legal awareness, developing effective dispute resolution mechanisms, and strengthening relevant institutions.